Elaboración de un manual de procesos y procedimientos para la administración de una finca agropecuaria bajo el estándar de calidad ISO 9001:2015 - Cabrera Morocho, Ángel Fabián (2017)
It present thesis, is refers to a study on "elaboration of a MANUAL of processes and procedures for the administration of a FINCA agricultural low the standard of quality ISO 9001:2015", same that was born as result of it need of strengthen it administration, control and improvement continuous of it Finca agricultural of the Mr Alfonso Arias, located in the parish San Pedro of the blessed of the Canton Catamayo in it province of Loja; for this, is apply systematically them criteria regulatory established in the standard of the standard international ISO 9001, low which, is made the manual of processes and procedures for the administration of the Finca agricultural in study; for a better development is raised them following objectives specific: diagnosis of them processes agricultural current of the finca in study; Analysis of them processes standardized for the use rational of them resources human, material, financial and technological availa. The methodology used in the implementation of the present work was direct and participatory. Is made a diagnosis through the application of surveys, to determine them needs current and the feasibility of that the owner of the finca can implement the manual of processes and procedures. By the results of the diagnosis and the information collected of sources bibliografico-documentales, is developed the Manual of processes and procedures. Them results analyzed depending on the standard ISO 9001, show that the system of management of quality of the Organization, responsibilities of the team management, management of resources of the Organization, realization of them products of the company, measurement, analysis and improves of them services and of the SGC, presents a level of maturity 1, within a range of qualification of the 1 to the 5; i.e. missing processes in the map, there are good practices but require improvement. By what the manual is be viable or executable, as will improve the processes, synthesize them procedures of work, and will contribute to it improves of the conditions labour of the personal; is sustainable for its permanence in the time, guaranteeing an administration more efficient and effective. It is concluded that management and technical management of the agricultural estate is not suitable for development as producers and suppliers to the local market, it is necessary to the implementation of modern management tools, focused and designed for the transformation of productive family farms; There is a stalemate in which live our producers in the development productive continuous; This, due to the limited training, advice and motivation to search greater opportunities in the market today. Is recommended to maintain the application of the criteria set out in the present manual; so on a time scale defined by them is to evaluate the results of its application, as well as search training and the National University of Loja will strengthen the implementation of training workshops on the development of models of quality management.